2016
DOI: 10.2147/bctt.s105563
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of <em>CYP2D6*2</em>, <em>CYP2D6*4</em>, <em>CYP2D6*10</em>, and <em>CYP3A5*3</em> in Thai breast cancer patients undergoing tamoxifen treatment

Abstract: BackgroundTamoxifen (TAM) is used in breast cancer treatment, but interindividual variabilities in TAM-metabolizing enzymes exist and have been linked to single nucleotide polymorphisms in the respective encoding genes. The different alleles and genotypes of these genes have been presented for Caucasians and Asians. This study aimed to explore the prevalence of the incomplete functional alleles and genotypes of the CYP2D6 and CYP3A5 genes in Thai breast cancer patients undergoing TAM treatment.Patients and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…The demographic data of the patients have been described in previous research 18. In brief, these patients demonstrated stage 0–IV breast cancer.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The demographic data of the patients have been described in previous research 18. In brief, these patients demonstrated stage 0–IV breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Early researches suggested that CYP2D6*10/*10 patients had shorter disease-free survival than heterozygous CYP2D6*10 ( p =0.046)17 and lower END concentrations than those patients with CYP2D6*1/*10 and CYP2D6*1/*1 ( p =0.045)19 among Thai breast cancer patients; however, the result was not completely generalized to target population because of the limited sample size 19. Furthermore, the associations between CYP3A5 polymorphisms and levels of TAM and its metabolites have never been explored in Thai breast cancer patients, even though a high prevalence of CYP3A5 incomplete allele ( CYP3A5*3 ) has been suggested in a previous study 18. The purpose of the present study was to determine the associations of CYP2D6 and CYP3A5 polymorphisms and the concentrations of TAM and its metabolites in large numbers of Thai breast cancer patients undergoing TAM treatment.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations